Cholesterol as a key player in amyloid β-mediated toxicity in Alzheimer’s disease - Rudajev, Vladimir; Novotny, Jiri (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder that is one of the most devastating and widespread diseases worldwide, mainly affecting the aging population. One of the key factors contributing to AD-related neurotoxicity is the production and aggregation of amyloid β (Aβ). Many studies have shown the ability of Aβ to bind to the cell membrane and disrupt its structure, leading to cell death. Because amyloid damage affects different parts of the brain differently, it seems likely that not only Aβ but also the nature of the membrane interface with which the amyloid interacts, helps determine the final neurotoxic effect. Because cholesterol is the dominant component of the plasma membrane, it plays an important role in Aβ-induced toxicity. Elevated cholesterol levels and their regulation by statins have been shown to be important factors influencing the progression of neurodegeneration. However, data from many studies have shown that cholesterol has both neuroprotective and aggravating effects in relation to the development of AD. In this review, we attempt to summarize recent findings on the role of cholesterol in Aβ toxicity mediated by membrane binding in the pathogenesis of AD and to consider it in the broader context of the lipid composition of cell membranes.